"What is reconciliation and are we there yet?" Different types and levels of reconciliation: A case study of Bosnia and Herzegovina. Issue 4 (2nd October 2017) - Strupinskienė, Lina
ABSTRACT: This article uses the northwestern Bosnian village of Prijedor as a case study to empirically engage with theoretical debates about how to understand and research reconciliation and its causes in postconflict societies. It starts with a review of almost 60 different academic definitions of reconciliation with a goal to map out a comprehensive overview of various types and levels of the phenomenon. It then tests the theoretical analytical 18-box matrix devised with data gathered in Prijedor (BiH) during two consecutive periods of fieldwork in order to further improve it and to introduce a temporal dimension into the research of reconciliation.